N-Methylpyridinium-4-Phenolates: Generation of a Betaine Dye Library Bearing Different Spacer Units and Their Solvatochromism - Dominguez-Caru, M (Wiley-Blackwell, 2016)
A library of thirteen N-methylpyridinium-4-phenolate betaine dyes was synthesized from 4-(4-methoxyphenyl)pyridines in a three step procedure involving N-methylation, a subsequent O-demethylation, and a final deprotonation. Their general structure comprised an electron-donating phenolate group and an electron-accepting 2,6-disubstituted-N-methylpyridinium moiety, connected either directly, or by a carbon-carbon double or triple bond. Their UV-Vis spectroscopic behavior exhibits a borderline inverted solvatochromism in a wide range of solvents with different polarities, changing from bathochromic to hypsochromic shifts with the increase of the solvent polarity. Inserting a double- or a triple-bond spacer between the donor and acceptor rings had the effect of increasing the solvatochromic sensitivity of the resulting dyes. © 2016 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim